The treatment efficacy of cortical bone trajectory (CBT) pedicle screws for lumbar degenerative disease in the Chinese Han population - Wu, Jinhui; Lin, Tao; Jiang, Heng; Ma, Jun; Zhang, Ke; Zhao, Jianquan; Zhou, Xuhui; Wang, Ce (Frontiers in Surgery, 2022)
Purposes: To assess the treatment efficacy of lumbar degenerative disease by CBT pedicle screws, and to give the referenced data of CBT pedicle screws from CT measurement of L1 to L5 in Chinese Han population. Methods: A total of 36 patients were included in this study for clinical and radiographic evaluation. Demographic characteristics, health related quality of life (HRQOL), and extent of intervertebral disc herniation and spondylolisthesis were evaluated. 100 patients searching from the CT database for CBT morphometric measurement of lumbar spine were then done. According to gender and age, patients were divided in 4 groups. The diameter, length, and the angle of the vertebral pedicle and trajectory were measured. Results: All patients’ neurological function and health related quality of life were significantly improved at final follow up (p<0.0001), and 75% patients achieved satisfaction. The mean diameter and the mean length varied from L1 to L5 in Group I to IV. The lateral angle ranged from L1 to L5 were 8.9 to 9.2°, 8.7 to 12.2°, 8.7 to 11.2°, and 9.2 to 10.1° in Group I to IV respectively. The cephalad angle from L1 to L5 were 23.5 to 28.6°, 24.7 to 26.6°, 25.0 to 28.2°, and 24.7 to 27.9° in Group I to IV respectively. Conclusions: CBT pedicle screws were effective in treating lumbar degenerative diseases and benefited the patients. The morphology of the lumbar vertebral pedicle varied from L1 to L5, and the trajectory was feasible and safe.